Genomic profiling of papillary renal cell tumours identifies small regions of DNA alterations: a possible role of HNF1B in tumour development - Szponar, Adrianna; Yusenko, Maria V; Kuiper, Roland; van Kessel, Ad Geurts; Kovacs, Gyula (Histopathology, 2011)
Szponar A, Yusenko M V, Kuiper R, van Kessel A G & Kovacs G (2011) Histopathology 58, 934-943 Genomic profiling of papillary renal cell tumours identifies small regions of DNA alterations: a possible role of HNF1B in tumour development Aims: Papillary renal cell tumours (RCT) are characterized by specific trisomies. The aim of this study was to identify small regions of duplication marking putative tumour genes. Methods and results: Full-tiling path bacterial artificial chromosome (BAC) array hybridization of 20 papillary RCTs confirmed the duplication of chromosomes 7 and 17 and also displayed smaller regions of gains/amplifications of 1.3-13.1 Mb in size. Detailed analysis showed a microamplification of BAC clones containing the MET at the 7q31.2 and also amplification of a DNA segment harbouring the transcription factor hepatocyte nuclear factor 1 beta (HNF1B) at chromosome 17q12. Nuclear expression of HNF1B protein was detected in 38 of 67 papillary RCTs, in five of five mucinous tubular and spindle cell carcinomas (MTSCC) and five of five metanephric adenomas by immunohistochemistry. Moreover, nine nephrogenic rests containing tubular differentiated structures and all 14 and five precursor lesions associated with papillary RCTs and MTSCCs, respectively, showed strong nuclear positivity when compared to the expression level in proximal tubules of the corresponding normal kidney. Conclusions: Our findings indicate a role of HNF1B in association with the high frequency of chromosome 17q duplication in the development of papillary RCTs and MTSCCs as well as in their precursor lesions.
Gesehen am 26.10.2022